Atypical exanthem with acral involvement in adult patients associated with human herpesvirus 7 active replication: A case series - Michelerio, Andrea; Tchich, Adi; Vassallo, Camilla; Brazzelli, Valeria (Frontiers in Medicine, 2023)
An “atypical exanthem” (AE) is an eruptive skin eruption that differs in morphology and etiology from classical exanthems and is often a reason for urgent medical evaluation. The most frequent cause of AEs is a viral infection, but an accurate etiology cannot be established basing on the sole clinical features. Human herpesviruses (HHV) have been often suspected as etiologic agents or cofactors in atypical rashes. We performed a retrospective analysis of adult patients presenting an atypical exanthem associated with HHV-7 active replication in our center. The charts of patients were reviewed and the demographic, clinical and laboratory data collected. Nine patients (six males and three females) were included in the study, with a mean age of 43 years for men and of 26 years for women. All patients presented active HHV-7 replication in plasma during the rash, which turned negative after the exanthem resolved. The exanthem displayed a maculopapular pattern involving the trunk, limbs and, notably, the acral regions, in six patients. In three cases the exanthem was confined to only the acral sites. In most cases, there was no fever and the inflammatory indices remained unchanged. Antihistamines, topical and systemic corticosteroids were used as treatment, with excellent symptom control. We propose adding skin manifestation associated with HHV-7 to the concept of atypical exanthems, in particular those localized to the acral regions.